[18F]Fludeoxyglucose-Positron Emission Tomography Evidence for Cerebral Hypermetabolism in the Awake State in Narcolepsy and Idiopathic Hypersomnia - Dauvilliers, Yves; Evangelista, Elisa; de Verbizier, Delphine; Barateau, Lucie; Peigneux, Philippe (Frontiers in Neurology, 2017)
Background: Changes in structural and functional central nervous system have been reported in narcolepsy, with large discrepancies between studies. No study has investigated yet spontaneous brain activity at wake in idiopathic hypersomnia. We compared relative changes in regional brain metabolism in two central hypersomnia conditions with different clinical features, namely narcolepsy type 1 and idiopathic hypersomnia, and in healthy controls. Methods: Sixteen patients (12 males, median age 30 years [17–78]) with narcolepsy type 1, nine patients (2 males, median age 27 years [20–60]) with idiopathic hypersomnia and 19 healthy controls (16 males, median age 36 years [17–78]) were included. 18F-fludeoxyglucose positron emission tomography (PET) was performed in all drug-free subjects under similar conditions and instructions to stay in a wake resting state. Results: We found increased metabolism in the anterior and middle cingulate and the insula in the two pathological conditions as compared to healthy controls. The reverse contrast failed to evidence hypometabolism in patients vs. controls. Comparisons between patient groups were non significant. At sub-statistical threshold, we found higher right superior occipital gyrus glucose metabolism in narcolepsy and higher middle orbital cortex and supplementary motor area metabolism in idiopathic hypersomnia, findings that require further confirmation. Conclusions: There is significant hypermetabolism in narcolepsy and idiopathic hypersomnia in the wake resting state in a set of brain regions constitutive of the salience cortical network that may reflect a compensatory neurocircuitry activity secondary to sleepiness. Metabolic differences between the two disorders within the executive-control network may be a signature of abnormally functioning neural system leading to persistent drowsiness typical of idiopathic hypersomnia.